2018
DOI: 10.1016/j.jsps.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antioxidative and antiviral biomarkers β-amyrin, β-sitosterol, lupeol, ursolic acid in Guiera senegalensis leaves extract by validated HPTLC methods

Abstract: J.F. Gmel is a broad-spectrum African folk- medicinal plant, having activities against fowlpox and herpes viruses. Very recently, we have shown the anti-hepatitis B vius (HBV) potential of leaves extract (GSLE). Here, we report the antioxidative and hepatoprotective efficacy of GSLE, including HPTLC quantification of four biomarkers of known antioxidative and antiviral activities. In cultured liver cells (HuH7) GSLE attenuated DCFH-induced oxidative stress and cytotoxicity. This was supported by DPPH radical-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 50 publications
4
35
1
Order By: Relevance
“…Others researchers found that lupeol acetate ameliorates collagen-induced arthritis through suppression of inflammatory cytokines and inhibition of bone erosion [24]. Indeed, the potential antioxidant and free radical scavenging effects of amyrin and lupeol have been demonstrated both in vitro and in vivo [25][26][27][28]. A recent report showed increased antioxidant activity and suppressed proinflammatory cytokine expressions in obese OA rats fed with SNO, further consolidating our previous findings [29].…”
Section: Introductionsupporting
confidence: 65%
“…Others researchers found that lupeol acetate ameliorates collagen-induced arthritis through suppression of inflammatory cytokines and inhibition of bone erosion [24]. Indeed, the potential antioxidant and free radical scavenging effects of amyrin and lupeol have been demonstrated both in vitro and in vivo [25][26][27][28]. A recent report showed increased antioxidant activity and suppressed proinflammatory cytokine expressions in obese OA rats fed with SNO, further consolidating our previous findings [29].…”
Section: Introductionsupporting
confidence: 65%
“…34 β-sitosterol shows antiviral effect against Hepatitis B Virus, HIV virus and tobacco mosaic virus (TMV). 33 First time reported from L. reticulata in this study, γ-sitosterol or Clionasterol was found in MSE (12.54%), EALE (6.86%), EASE (6.35%) and EARE (2.59%). γ-sitosterol shows anticancerous, 35 hepatoprotective, anti-hyperglycemic activity and may act as a potential antidiabetic drug.…”
Section: Steroidsmentioning
confidence: 51%
“…It was absent in all ethyl acetate extracts. β-sitosterol shows various biological activities like immunomodulatory, antioxidative, hepatoprotective activity 33 and used in the treatment of benign prostatic hyperplasia. 34 β-sitosterol shows antiviral effect against Hepatitis B Virus, HIV virus and tobacco mosaic virus (TMV).…”
Section: Steroidsmentioning
confidence: 99%
“…Strychnos spinosa [25] Acanthophora spicifera [26] Cladophora fascicularis [27] Sargassum muticum [28] Antitrypanosomal [25] Anti-obesity, [28] a novel selective LXRb agonist, [29] and anticancer activities [30] b-sitosterol (4) Terrestrial plant Red macroalgae Green macroalgae Brown macroalgae Microalgae Synadenium glaucescens [31] Eucheuma cottonii [32] Ulva fasciata [33] Sargassum glaucescens [34] Nannochloropsis [35] Antimicrobial, [36] antiviral activity against hepatitis B virus, [37] antioxidant and anticancer activities [38] Glycoglycerolipids (5,9) Terrestrial plant Red macroalgae Brown macroalgae Cyanobacteria Soybean [39] Exophyllum wentii [40] Sargassum horneri [41] Phormidium sp. [42] Accumulation inhibition, [39] antitumor, antiviral, anti-inflammatory and anticancr activities [30,43] Kjellmanianone (6) Brown macroalgae Sargassum naozhouense [44] Antibacterial effect against E. coli and Bacillus subtilis [45] Loliolide 7Terrestrial plant Brown macroalgae…”
Section: Introductionmentioning
confidence: 99%